TRANSIENT STABILITY ANALYSIS OF GRID CONNECTED FUEL CELL SYSTEM - Rahman, Md. Ashifur; Shawon, Mohammad Hasanuzzaman; Rahman, Md. Mostafizur; Hossain, Md. Shafayet (European Scientific Journal, ESJ, 2013)
Fuel Cell Technology has become quite popular now a days. Since it is a renewable energy source, the development of fuel cell technology has drawn much attention among the researchers and scientists over the last few years. The prime focus of this paper is to analyze and enhance the transient stability of a grid connected fuel cell system. A MATLAB/SIMULINK based fuel cell system has been implemented along with the proposed inverter control strategy. The purpose of this inverter control is to enhance the transient stability of the system. Another salient feature of this study is the inclusion of a Z source inverter with the grid connected fuel cell system. The simulation results are carried out to verify the inverter control strategy under different fault condition. Finally, this paper presents transient analysis of a grid connected fuel cell system including detail simulation results in MATLAB/SIMULINK environment.